Effects of foundry industry on the environment - N. Šehić-Mušić; Š. Goletić; D. Pihura; L. Mušić; K. Hasanović (Metalurgija, 2013)
Integrating environment development, as the objective of the research in this paper, is to define a model to implement and monitor the key indicators of energy use efficiency as an instrument of an effective environmental and energy management in the metal sector in Bosnia and Herzegovina (B&H). The used environmental data contribute to a more efficient use of energy as well as to a reduction of emissions and effects on the environment.